Comparison of 7- and 14-day first-line therapies including levofloxacin in patients with Helicobacter pylori positive non-ulcer dyspepsia - Cemal Nuri ERÇİN; Ahmet UYGUN; Ahmet Burak TOROS; Murat KANTARCIOĞLU; Güldem KİLCİLER; Zülfikar POLAT; Sait Bağcı (Turkish Journal of Gastroenterology, 2019)
-